Reaching gen z skincare consumers in Portugal: how can myclarins integrate and promote wellness - Pinto, Mariana Oliveira (2024)
Positioned within the legacy prestige brand Clarins, the myClarins’ product range was introduced to meet the needs of Gen Z consumers. The following Work Project intended to gather insights into myClarins’ current context and propose recommendations tailored to the Portuguese market. Along with a proposed unique selling proposition, the classification of myClarins as a sub-brand rather than a product range is recommended. In this sense, this report was outlined to provide research based directions myClarins can adopt to reach and engage the desired target, Gen Z .Concretely, the individual section of this report focuses on a wellness-based communication strategy.